Surely not!Between certainty and disbelief - Graham Ranger (Discours)
The marker surely possesses at least three different functions: as an intrapredicative adverb of manner, an extrapredicative epistemic adverb and a discourse adverb. In this paper I will propose a single characterisation of surely within the framework of the Theory of Enunciative Operations (cf. Culioli, 1990, 1999a and 1999b). We will see that, depending on variable contextual parameters, surely assumes one of its three possible values. More precisely, surely marks a correspondence between, on the one hand, a preconstructed trajectory leading from a start point to an end point (from (p, non-p) to p), and on the other, the same trajectory constructed in the speech situation by the speaker. When the trajectory bears upon the mode of realisation of a process, surely assumes its intrapredicative value, when it bears upon the passage from a source situation to a projected situation, surely functions extrapredicatively, as an epistemic adverb. The discourse adverb function of surely poses some problems for analysis. When epistemic, surely appears to mark certainty, but when discursive, it appears rather to mark doubt, disbelief or incomprehension, according to context. I propose that when surely is used in this way, it marks the speaker’s endorsement of a preconstructed trajectory while also acknowledging the presence of a preconstructed, counteroriented trajectory, endorsed by another speaker. The shift from certainty to doubt might be explained as the consequence of the speaker’s recognition of a wider discursive context. The various contextual values of the discourse adverb surely (cf. Downing, 2001, for example) depend, among other factors, on how the speaker positions his or her discourse relative to other enunciative instances.